Barriers, facilitators, and resources to opioid deprescribing in primary care: experiences of general practitioners in Australia. Issue 4 (11th April 2022) - Hamilton, Melanie; Mathieson, Stephanie; Gnjidic, Danijela; Jansen, Jesse; Weir, Kristie; Shaheed, Christina A.; Blyth, Fiona; Lin, Chung-Wei C.
Abstract : While general practitioners emphasised the importance of deprescribing opioids, key barriers related to the process being time consuming and having limited resources and support. Abstract: Deprescribing is the systematic process of discontinuing drugs when harms outweigh the benefits. We conducted semistructured telephone interviews with 22 general practitioners (GPs) who had prescribed or deprescribed opioids in patients with chronic noncancer pain within the past 6 months to investigate the barriers and facilitators to deprescribing opioid analgesics in patients with chronic noncancer pain. We also explored GPs' perspectives on the available resources to assist them with opioid deprescribing. Interviews were audio-recorded, transcribed verbatim, and then coded using an iterative process until data saturation reached. The thematic analysis process identified themes, first as concepts, and then refined to overarching themes after the merging of similar subthemes. Themes exploring barriers to deprescribing highlighted the difficulties GPs face while considering patient factors and varying prescribing practices within the confines of the health system. Patient motivation and doctor–patient rapport were central factors to facilitate deprescribing and GPs considered the most important deprescribing resource to be a multidisciplinary network of clinicians to support themselves and their patients. Therefore, although GPs emphasised the importance of deprescribing opioid analgesics, they also expressed many barriers relating to managing complex pain conditions, patient factors, and varying prescribing practices between clinicians. Some of these barriers could be mitigated by GPs having time and resources to educate and build rapport with their patients. This suggests the need for further development of multimodal resources and improved support through the public health system to enable GPs to prioritise patient-centred care.